First report of a novel liquid nitrogen adjustable flow spray cryotherapy (SCT) device in the bronchoscopic treatment of disease of the central tracheo-bronchial airways - Browning, Robert; Parrish, Scott; Sarkar, Saiyad; Turner Jr, J. Francis (Journal of Thoracic Disease, 2013)
Cryotherapy has been employed as a modality in the airways for many years. It’s use in the airway has been limited to the cryoprobe which requires direct contact with the tissue (1,2). Endoscopic spray cryotherapy (SCT) using liquid nitrogen as the cryogen was initially developed for endoscopic use in mucosal ablation in 1999 with subsequent indications for the treatment of esophageal malignancies (3,4).